Análise da estabilidade genética na micropropagação de cattleya elongata barb. rodr., orquídea endêmica da Chapada Diamantina-Ba - Nascimento, Gustavo Surlo (2020)
Cattleya elongata is endemic specie of Chapada Diamantina with high ornamental value, which makes it a victim of predatory extraction. In this context, tissues culture can generate many plants in a reduced time. However, the technique can promote the occurrence of somaclonal variation (SV) in produced plants. The present study aimed to verify the occurrence and understand the dynamics of SV during in vitro multiplication of C. elongata using ISSR (Inter Simple Sequence Repeat) markers. For the plants obtained through direct organogenesis over seven generations of subculture, SV was detected in 36.8% of the analyzed genotypes, however, the plants carrying polymorphic loci still remained highly similar to the respective mother plants. Polymorphism was detected from the second generation of subculture. The genotype and the number of subcultures influenced the occurrence of SV. A new phenomenon based on the occurrence of chimeras in vitro may justify part of the variation in haplotypes. It was found that the formation of shoots from callus was due to organogenesis. Although 26% of the analyzed calli presented polymorphic loci when compared to their respective mother plants, none of the 103 regenerated plants from them presented SV, which is attributed to the probable deleterious effect of SV during the organogenesis of shoots. Therefore, an attempt was made to clarify the dynamics of SV during in vitro cultivation of C. elongata, which may provide a basis not only for the in vitro cultivation of the species, but also turn it a model object to understand several phenomena.